Respuesta :

Answer:

The answer is B,

Step-by-step explanation:

I got it right on the test

Answer:

[tex](-\frac{1}{2} )^{-3}[/tex]

Step-by-step explanation:

Let us apply the following law of exponents to simplify all the options.

[tex]a^{-m}=\frac{1}{a^{m}}[/tex]


For the first option, we have

[tex]-2^{-3}=\frac{1}{-2^3} =-\frac{1}{2\times 2\times 2\times 2} =-\frac{1}{8}[/tex]


For the second expression, we have,


[tex](-\frac{1}{2})^{-3}=\frac{1}{(-\frac{1}{2})^3}[/tex]


[tex]=\frac{1}{-\frac{1}{2}\times -\frac{1}{2} \times -\frac{1}{2} }[/tex]


[tex]=\frac{1}{-\frac{1}{8} }[/tex]


[tex]=-1\times \frac{8}{1}=-8[/tex]


For the third expression, we have,


[tex](\frac{1}{2})^{-3}=\frac{1}{(\frac{1}{2})^3}[/tex]


[tex]=\frac{1}{\frac{1}{2}\times \frac{1}{2} \times \frac{1}{2} }[/tex]


[tex]=\frac{1}{\frac{1}{8} }[/tex]


[tex]=1\times \frac{8}{1}=8[/tex]


For the last option, we have

[tex]2^{-3}=\frac{1}{2^3} =\frac{1}{2\times 2\times 2\times 2} =\frac{1}{8}[/tex]


Hence the correct answer is B.